THE QUALITY OF ADMINISTRATIVE SERVICES - Sugiato, Fiki; Tohopi, Rustam; Nani, Yacob Noho (Public Policy Journal, 2024)
This study aims to determine how the Quality of Administrative Services of the Togean District Office of Tojo Una-Una Regency is seen from five dimensions, namely (a) tangibles (physical evidence), (b) reliability, (c) responsiveness, (d) assurance, and (e) empathy. This research uses a qualitative approach method with a descriptive qualitative research type while the data collection techniques used are observation, interviews, and documentation. Based on the research results obtained, it can be concluded that the results of this study are in the aspect of physical evidence, the Togean sub-district office has not fulfilled adequate service facilities, in the aspect of reliability, the community is satisfied with the services provided, in the aspect of responsiveness, employees are willing to help the difficulties experienced by visitors, from the aspect of assurance, especially the responsibility of each has not been maximized due to the lack of existing facilities, in the empathy aspect, which the Alla Sub-district gives by giving a pleasant impression. The author suggests that the sub-district government further improve the quality of service that is considered unsatisfactory in the service process, namely the dimension of physical facilities so that people can feel satisfied and comfortable when receiving services.